In vivo Cerenkov luminescence imaging: a new tool for molecular imaging - Mitchell, Gregory S. (The Royal Society Publishing, 2011)
Cerenkov radiation is a phenomenon where optical photons are emitted when a charged particle moves faster than the speed of light for the medium in which it travels. Recently, we and others have discovered that measurable visible light due to the Cerenkov effect is produced in vivo following the administration of β-emitting radionuclides to small animals. Furthermore, the amounts of injected activity required to produce a detectable signal are consistent with small-animal molecular imaging applications. This surprising observation has led to the development of a new hybrid molecular imaging modality known as Cerenkov luminescence imaging (CLI), which allows the spatial distribution of biomolecules labelled with β-emitting radionuclides to be imaged in vivo using sensitive charge-coupled device cameras. We review the physics of Cerenkov radiation as it relates to molecular imaging, present simulation results for light intensity and spatial distribution, and show an example of CLI in a mouse cancer model. CLI allows many common radiotracers to be imaged in widely available in vivo optical imaging systems, and, more importantly, provides a pathway for directly imaging β(−)-emitting radionuclides that are being developed for therapeutic applications in cancer and that are not readily imaged by existing methods.